1985
DOI: 10.1016/0014-5793(85)80664-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective labeling of beef heart cytochrome oxidase subunit III with eosin‐5‐maleimide

Abstract: Cytochrome c oxidase has been isolated from beef heart mitochondria and labeled with the fluorochrome eosin-5-maleimide (EMA) after pretreatment with mersalyl. On SDS-polyacrylamide gels, EMA fluorescence and absorption occurred at a single band corresponding to subunit III. Since only Cys 115 of the two cysteinyl residues of subunit III had been shown to be reactive towards water-soluble SH-reagents, it was concluded that this residue was the one labeled by EMA. The EMA/enzyme ratio was about 1. Gel filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In the late 1980s Malatesta and Capaldi (41) showed that iodoacetamide, at a 1:1 molar ratio, reacts exclusively with cysteine 115 on subunit III. Incubation of the enzyme with eosin-5maleimide also resulted in binding at the same site (42). In the present study, the incubation of bovine cytochrome c oxidase with fluorescein maleimide (at 1:1 molar ratio) for 20 min at 25 °C resulted in selective labeling (∼90%) of subunit III as verified by SDS gel electrophoresis.…”
Section: Resultssupporting
confidence: 65%
“…In the late 1980s Malatesta and Capaldi (41) showed that iodoacetamide, at a 1:1 molar ratio, reacts exclusively with cysteine 115 on subunit III. Incubation of the enzyme with eosin-5maleimide also resulted in binding at the same site (42). In the present study, the incubation of bovine cytochrome c oxidase with fluorescein maleimide (at 1:1 molar ratio) for 20 min at 25 °C resulted in selective labeling (∼90%) of subunit III as verified by SDS gel electrophoresis.…”
Section: Resultssupporting
confidence: 65%
“…The reaction with iodoacetamide blocks the formation of the complex with yeast cytochrome c indicating that (2115 is on the cytoplasmic side. Muller and Azzi [37] have shown that, following pretreatment with mersalyl, eosin 5-maleimide can be specifically incorporated into subunit 111 (presumably at C115); this modification should greatly facilitate the study of subunit 111 removal and reassociation.…”
Section: Chemical Modification Ojsuhunit 111mentioning
confidence: 99%
“…Cys-115 of subunit III is the sulfhydryl in cytochrome oxidase most reactive to hydrophilic sulfhydryl reagents, and Cys-115 can be labeled selectively under appropriate conditions (McGeer et al, 1977;Hall et al, 1988;Malatesta & Capaldi, 1982; Muller & Azzi, 1985). Yang et al (1984) have described the synthesis of an undecagold cluster compound containing a single maleimide group which can be used to label selectively cysteine sulfhydryl groups.…”
mentioning
confidence: 99%